Multiple Lipomas on the tongue: A rarity in location and in number - Lee, Sang Min; An, Ae Ri; Ko, Seung-O (The Korean Journal of Oral and Maxillofacial Pathology, 2019)
Objectives: Lipoma is the most common soft tissue mesenchymal tumor which grows slowly. [1] [2] Intraoral lipomas are rare and have been reported in approximately 1 to 4% of all neoplasm in various literature. [2-5] Oral lipomas mostly develop slowly without symptoms, [6] and predominantly affect the buccal mucosa, floor of mouth, tongue and lip. [3] Material and Methods: A 71-year old male presented with asymptomatic swelling on tongue. On the clinical examination, there were various size of three swelling areas on the dorsum of tongue. Result: All lesions were surgically removed via intraoral approach under general anesthesia. They were soft and yellowish in color. All of the specimens has histologically revealed as typical lipomas. Conclusion: It is a report of tongue lipomas as a rare site, with clinical, histological and radiographic features. Also, there were several reports of a large or huge lipoma in oral cavity, however there were no report of multiple lipomas on the tongue. So, authors report the rarity of it. KCI Citation Count: 0